ANTIFUNGAL EFFECTIVENESS OF BAJAKAH ROOT EXTRACT (Uncaria acida) AGAINST THE ACTIVITY OF Malassezia furfur, THE CAUSATIVE AGENT OF SEBORRHEIC DERMATITIS IN MICE - Ira Wahyu Ningsih; Mukhlis Rohmadi; Lilin Ika Nur Indahsari (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Seborrheic dermatitis is a chronic skin disorder associated with colonization by Malassezia furfur and is commonly treated with topical antifungal agents and corticosteroids, which may cause adverse effects when used long term. Therefore, safer and more sustainable alternative therapies derived from natural products are needed. One such candidate is bajakah root (Uncaria acida), which is known to contain flavonoids, alkaloids, tannins, terpenoids, and saponins with potential antifungal activity. This study employed a true experimental posttest-only design involving 24 male BALB/c mice induced with Malassezia furfur and divided into a negative control group (distilled water), a positive control group (ketoconazole), and treatment groups receiving Uncaria acida extract at concentrations of 25%, 50%, 75%, and 100%. The research stages included extr act preparation using ethanol maceration, ointment formulation, fungal infection induction, and clinical evaluation. Phytochemical analysis confirmed a total flavonoid content of 28.5 mg QE/g. The results demonstrated significant differences across all clinical parameters (p < 0.05), with the 75% extract concentration providing the most optimal clinical improvement. These findings indicate that Uncaria acida extract has strong potential for development as a topical herbal therapeutic candidate and provides a foundation for further studies focusing on formulation optimization and clinical trials.